2022
DOI: 10.1039/d1tc06110k
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective Sb-doped SnO2 films as stable and efficient alternative transparent conducting electrodes for dye-sensitized solar cells

Abstract: Indium tin oxide (ITO) is an ubiquitous transparent conducting oxide (TCO) used in various optoelectronic devices owing to its high optical transmittance and high electrical conductivity. The rarity of indium...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Last but not least, PSCs require corrosion‐resistant electrodes with high conductivity and matching energy levels, [131] such as alloying metals (e. g., Au, Ag or Cu), [132–134] TCOs (e. g., ITO, FTO, ATO or AZO) [135–138] and carbon‐based materials (e. g., graphene, carbon nanotubes or conductive polymers) [139–141] …”
Section: Causes Of Redox Reactions and Specific Countermeasuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Last but not least, PSCs require corrosion‐resistant electrodes with high conductivity and matching energy levels, [131] such as alloying metals (e. g., Au, Ag or Cu), [132–134] TCOs (e. g., ITO, FTO, ATO or AZO) [135–138] and carbon‐based materials (e. g., graphene, carbon nanotubes or conductive polymers) [139–141] …”
Section: Causes Of Redox Reactions and Specific Countermeasuresmentioning
confidence: 99%
“…Last but not least, PSCs require corrosion-resistant electrodes with high conductivity and matching energy levels, [131] such as alloying metals (e. g., Au, Ag or Cu), [132][133][134] TCOs (e. g., ITO, FTO, ATO or AZO) [135][136][137][138] and carbon-based materials (e. g., graphene, carbon nanotubes or conductive polymers). [139][140][141] Furthermore, several common transparent metal oxide electron (e. g., ZnO, TiO 2 , SnO 2 ) and hole (e. g., NiO x , MoO x or CuO x ) transport materials will inevitably produce problematic hydroxyl group-rich oxides.…”
Section: Interface Layermentioning
confidence: 99%
“…16,17 Elemental mixing and semiconductor compounding are the two most commonly used modification methods for SnO 2 . Elemental mixing is mainly used in the field of battery research, and different types of elements can achieve different modification effects: Sb 18 and Yb 19 can improve the conductivity, Ag 20 can improve the arc erosion performance, and Er 21 and Pb 22 can improve the optical emission performance. A semiconductor composite is commonly used in the field of photocatalysis, such as TiO 2 , 23 Bi 12 O 15 C l6 , 24 g-C 3 N 4 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that a +5 charge state exists when Sb is replaced in the SnO2 lattice. The literature [11] demonstrated that the doping of Sb into the SnO2 lattice leads to an improvement in the properties and performance of DSSCs. Its increased hydrophilicity compared to the undoped SnO2 electrode and the merit value of the doped electrode is 8.23, and the thin layer resistance value is 12.…”
Section: Introductionmentioning
confidence: 99%
“…Danjuan Liu, Wei He and Siyong Fu. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] …”
mentioning
confidence: 99%